2022
DOI: 10.1177/02692155221110727
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy for facial nerve paralysis (Bell's palsy): An updated and extended systematic review of the evidence for facial exercise therapy

Abstract: Objective To conduct a systematic review of the effectiveness of facial exercise therapy for facial palsy patients, updating an earlier broader Cochrane review; and to provide evidence to inform the development of telerehabilitation for these patients. Data Sources MEDLINE, EMBASE, CINAHL, Cochrane Library, PEDro and AMED for relevant studies published between 01 January 2011 and 30 September 2020. Methods Predetermined inclusion/exclusion criteria were utilised to shortlist abstracts. Two reviewers independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 89 publications
1
18
0
2
Order By: Relevance
“…As highlighted in the 2022 systematic review by Khan et al , the heterogeneity of and lack of standardization among facial rehabilitation programs complicates evaluations of the outcomes of such approaches. In their evaluation of the efficacy of facial exercise therapy among patients diagnosed with Bell's palsy, Khan et al concluded that facial rehabilitation does provide a benefit to patients with facial paralysis in both the acute and chronic phases of recovery, however their inability to pool the data precluded any more specific conclusions [15 ▪ ].…”
Section: Facial Rehabilitationmentioning
confidence: 99%
“…As highlighted in the 2022 systematic review by Khan et al , the heterogeneity of and lack of standardization among facial rehabilitation programs complicates evaluations of the outcomes of such approaches. In their evaluation of the efficacy of facial exercise therapy among patients diagnosed with Bell's palsy, Khan et al concluded that facial rehabilitation does provide a benefit to patients with facial paralysis in both the acute and chronic phases of recovery, however their inability to pool the data precluded any more specific conclusions [15 ▪ ].…”
Section: Facial Rehabilitationmentioning
confidence: 99%
“… 15 Techniques such as neuromuscular re-education, biofeedback, electrostimulation, and facial expression exercises are available, but they do not have a strong level of evidence. 5 , 15 , 16 The term “facial disability” was coined to describe patient’s quality of life impairments, such as eating and speaking handicaps, as well as the emotional and social aspects that this ailment can entail. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, early rehabilitation intervention in facial nerve patients has been reported to reduce complications and sequelae such as synkinesis and dry eye 6 . Moreover, synkinesis may arise from dysfunction in both the central and peripheral nervous systems, and the effectiveness of drug therapy such as botulinum toxin injections in addition to rehabilitation has also been demonstrated 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, synkinesis may arise from dysfunction in both the central and peripheral nervous systems, and the effectiveness of drug therapy such as botulinum toxin injections in addition to rehabilitation has also been demonstrated. 7 The electroneurography (ENoG) value of <40% and the ratio of the interpalpebral distance of <85% [8][9][10] have been reported to be correlated with the occurrence of synkinesis. Based on our previous studies, [11][12][13][14][15][16][17] we hypothesized that the characteristics of patients with early-onset facial paralysis measured with values of "ENoG," "the difference in the nerve excitability test (NET)," and "Yanagihara score" could be used to exquisitely predict facial synkinesis using machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%